Designing a Web-Based Vehicle Tracking Application using the Design Thinking Method - Amalia, Endang (AI Society & STMIK Indonesia, 2025)
The primary challenge faced by fleet managers in mining companies is the lack of sufficient visibility and control over their fleet operations. Without accurate, real-time information about the location, status, and performance of vehicles, companies may struggle to optimize routes, maintain fleet safety, and provide quality service to customers. Firm measures and strict supervision are necessary to ensure the continuity of mining product distribution. Therefore, a web-based application was designed to address these issues. In designing the web-based vehicle tracking application that aligns with user needs, the design thinking method was employed because this method places users at the core, ensuring that the resulting prototype truly meets users' needs and preferences. The prototype was then implemented as a web-based application using Vue.js and the OpenLayers Library to produce an application consisting of a login page, dashboard, vehicle tracking, device management, master data, violation, and reports that meet user needs based on acceptance criteria tested using the User Acceptance Test (UAT) method, thereby becoming a solution to users' needs.